2020
DOI: 10.3389/fpsyg.2020.564413
|View full text |Cite
|
Sign up to set email alerts
|

Western Diet: Implications for Brain Function and Behavior

Abstract: The Western diet (WD) pattern characterized by high daily intake of saturated fats and refined carbohydrates often leads to obesity and overweight, and it has been linked to cognitive impairment and emotional disorders in both animal models and humans. This dietary pattern alters the composition of gut microbiota, influencing brain function by different mechanisms involving the gut–brain axis. In addition, long-term exposure to highly palatable foods typical of WD could induce addictive-like eating behaviors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 185 publications
(196 reference statements)
0
74
0
1
Order By: Relevance
“…Moreover, Sonnenburg et al showed in humanized mice that the loss of diversity in the composition of GM after western diet (WD) intake was magnified over several successive generations [ 197 ]. This shift to an “unhealthy” microbiota composition induced by the WD influences brain function and induces addictive-like eating behaviors [ 198 ]. Studies conducted both in humans and animal models confirm that consumption of highly palatable food and ultra-processed food typical of WD is closely related to the development of these maladaptive habits [ 199 , 200 , 201 , 202 ].…”
Section: Interrelationship Between Gut Microbiota and Food Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Sonnenburg et al showed in humanized mice that the loss of diversity in the composition of GM after western diet (WD) intake was magnified over several successive generations [ 197 ]. This shift to an “unhealthy” microbiota composition induced by the WD influences brain function and induces addictive-like eating behaviors [ 198 ]. Studies conducted both in humans and animal models confirm that consumption of highly palatable food and ultra-processed food typical of WD is closely related to the development of these maladaptive habits [ 199 , 200 , 201 , 202 ].…”
Section: Interrelationship Between Gut Microbiota and Food Addictionmentioning
confidence: 99%
“…Based on these data, the vicious cycle hypothesis has been proposed. Accordingly, the diet provides the substrate for the GM, which modulates appetite by signaling the brain, and finally CNS mediates the preference for specific foods, and the cycle starts once more [ 198 ].…”
Section: Interrelationship Between Gut Microbiota and Food Addictionmentioning
confidence: 99%
“…Diet marked by a bigger share of saturated fats (butter, coconut oils, palm, cheese, and red meat) and refined carbohydrates (white bread, white flour, white rice, pizza dough, pasta, pastries, sweet desserts, and many breakfast cereals), generally referred to as “Western Diet” result in various lifestyle diseases/disorders such as type 2 diabetes, atherosclerosis, obesity, heart disease, and stroke. Reduced cognition and addiction‐like behavior have also been related to this diet pattern (López‐ et al., 2020). Most importantly, the key factors behind brain health issues are influenced by unhealthy diet patterns, and deficiency of essential nutrients, like minerals, vitamins, and omega‐3 fatty acids, among the individuals (Sathyanarayana Rao et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, consumption of diets with high levels of saturated fat and refined sugars is associated with impairments in memory performance, mood regulation, sensations, and motivated behaviors, and linked to an increased risk of neurological disorders such as Alzheimer’s, dementia, Parkinson’s, depression, and anxiety. Although studies have reported broad differences in inflammation, oxidative stress, neurochemicals, and neurogenesis with energy-dense diets and high body mass index (BMI; Luchsinger et al, 2002 ; López-Taboada et al, 2020 ), the specific molecular, cellular, and neural mechanisms remain to be discovered, and with them interventions that prevent or treat these diseases. To find answers researchers have turned to animal models.…”
Section: Introductionmentioning
confidence: 99%